2002
DOI: 10.1034/j.1399-3062.2002.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing immunosuppressive regimen on the incidence, duration, and viral load of cytomegalovirus infection in renal transplantation: a single center report

Abstract: Background. In this retrospective single center study we have evaluated the relation between the immunosuppressive regimen and the incidence and characteristics of cytomegalovirus (CMV) infection in the setting without CMV prophylaxis from 1989 through 1998. Methods. All (470) first cadaveric renal transplantations in nonsensitized (PRA < 60%) patients were analyzed. Immunosuppression consisted of cyclosporine A (Sandimmune) and prednisolone from 1989 through 2-1993 (S; 189 patients), of cyclosporine microemul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…4,33,34 Our findings clearly showed that the use of T cell-depleting antibodies such as Thymoglobulin increased the risk for CMV infection and disease compared with IL-2 receptor antagonists in CMV Dϩ/RϪ patients. In addition, our study suggests that the choice of CNIs CLINICAL RESEARCH www.jasn.org may influence the risk of CMV disease in this group of patients.…”
Section: Discussionmentioning
confidence: 68%
“…4,33,34 Our findings clearly showed that the use of T cell-depleting antibodies such as Thymoglobulin increased the risk for CMV infection and disease compared with IL-2 receptor antagonists in CMV Dϩ/RϪ patients. In addition, our study suggests that the choice of CNIs CLINICAL RESEARCH www.jasn.org may influence the risk of CMV disease in this group of patients.…”
Section: Discussionmentioning
confidence: 68%
“…During CMV infection, endothelial cells acquire a cytomegalic morphology (36) and can be detached from the vessel wall (36)(37)(38). Moreover, CMV infection increases the risk of coronary disease and of death in transplanted patients (39) and is linked to chronic transplant dysfunction (40 (48,49) that are reflected by higher CEC (50) and EMP levels (51). In addition, EMP (52) …”
Section: Al-massarani Et Almentioning
confidence: 99%
“…In a study by de Maar et al [6], 470 renal transplant recipients were retrospectively evaluated according to the immunosuppressive regimen used: cyclosporine (standard formulation) and prednisolone, versus cyclosporine (microemulsion formulation) and prednisolone, versus MMF and cyclosporine and prednisolone. Patients who received induction therapy with OKT3 or ATG were excluded, and gancyclovir was given preemptively.…”
Section: Risk Of Cytomegalovirus Infection In Transplant Recipientsmentioning
confidence: 99%
“…Additionally, CMV has been found to be an independent risk factor for the development of other infectious complications, such as bacteremias, invasive fungal diseases and Epstein Barr virus (EBV)-related post-transplant lymphoproliferative disease; it is also a cause of acute and chronic allograft injury [5]. There is a hypothesis that cytomegalovirus may cause endothelial damage in the transplanted organ, leading to chronic transplant dysfunction [6].…”
mentioning
confidence: 99%